Clinical characteristics of male prolactinoma patients mainly presenting with severe obesity and the metabolic response to dopamine agonist therapy - Wang, Linjie; Wang, Xiaojing; Gong, Fengying; Pan, Hui; Zhu, Huijuan (Frontiers in Endocrinology, 2023)
Objective To summarize the clinical characteristics of 4 male prolactinoma patients with severe obesity. Methods The clinical data of all the patients were retrospectively analyzed. Results All the patients visited our hospital for severe obesity at the age of 16-30 years old with their body mass index (BMI) of 37.9-55.9 kg/m 2 . All the patients were obese since childhood, even at birth. Hyperprolactinemia (72.3-273.0 ng/ml) was found during the etiological screening of obesity and MRI revealed pituitary adenomas. Additionally, all of them had multiple obesity related complications, such as hyperinsulinemia and dyslipidemia. Treatment of dopamine agonists (DAs) effectively normalized their prolactin level and the pituitary MRI reexamination after 6 months of DAs treatment showed the shrinkage of the pituitary adenomas in 3 patients. Their weight also decreased in different degrees (2.70~19.03% lower than the baseline) with improved metabolic profiles. Conclusion Serum prolactin level should be screened in obese patients, especially those with severe obesity.